2020
DOI: 10.1177/1090198119893692
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing Response Rates to Ads for Free At-Home HIV Testing on a Men-for-Men Geosocial Sexual Networking App: Lessons Learned and Implications for Researchers and Providers

Abstract: Internet-based recruitment can be effective in reaching large numbers of geographically diverse individuals. Geosocial sexual networking apps on smartphones have emerged as the modal way in which men who have sex with men (MSM) meet sex partners, and as venues for sexual health research. We report on the performance of three types of ads—text-only, text with male figure (no face), and text with male figure (with face)—used on a geosocial sexual networking app to advertise free at-home HIV testing and to enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…For reaching younger GBM and GBM from racialized and/or immigrant communities, a recent study in the US has found that pictured based digital advertisements on social/sexual networking mobile applications used by GBM to be effective in reaching young GBM and GBM of colour. 31 Increased community engagement and leadership in the design, delivery and scale-up of STBBI services may also increase uptake in these communities as well. 32 , 33 We have also found GCO to be a cost-effective alternative for HIV testing among GBM living in Vancouver, BC when compared to clinic-based HIV testing services, 34 which may encourage policy makers to consider implementing a similar service in Ontario.…”
Section: Discussionmentioning
confidence: 99%
“…For reaching younger GBM and GBM from racialized and/or immigrant communities, a recent study in the US has found that pictured based digital advertisements on social/sexual networking mobile applications used by GBM to be effective in reaching young GBM and GBM of colour. 31 Increased community engagement and leadership in the design, delivery and scale-up of STBBI services may also increase uptake in these communities as well. 32 , 33 We have also found GCO to be a cost-effective alternative for HIV testing among GBM living in Vancouver, BC when compared to clinic-based HIV testing services, 34 which may encourage policy makers to consider implementing a similar service in Ontario.…”
Section: Discussionmentioning
confidence: 99%
“…Social media and dating apps use blast advertisements with images and text, whereas search engines use text-only promotional content. Researchers attempting to identify the best type of advertisement to reach MSM through the internet for free at-home HIV testing [ 29 ] showed that the click-through rate for a text-only advertisement on Google was 0.38%, whereas that for advertisements with images, such as the ones used in social media and dating apps, was higher, between 0.77% and 2%.…”
Section: Discussionmentioning
confidence: 99%
“…Enrollment began in October 2017 using ads on men-for-men geosocial networking phone applications (apps) and concluded in June 2018. The cohort and study procedures have been fully described elsewhere [ 33 , 38 , 39 ]. Briefly, core eligibility criteria for enrollment specified that participants were aged 16 to 49; had at least two male sex partners in the prior 3 months; were not currently participating in an HIV vaccine or PrEP clinical trial; were not currently taking PrEP; lived in the U.S. or its territories; were not known to be HIV-positive; had a gender identity other than cisgender female; and reported behavioral risk for HIV.…”
Section: Methodsmentioning
confidence: 99%
“…These participants were invited to complete a baseline online survey via email. Of those, 6267 (71.6%) completed the baseline survey and received a $15 incentive [ 38 , 39 ]. Following completion of the survey, and for an additional $15 incentive, participants were mailed an at-home biospecimen collection device.…”
Section: Methodsmentioning
confidence: 99%